ANALISIS EFEKTIVITAS IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN - Anak Agung Gede Agung; Chindytia; Ni Made Gita Aristyawati; Ni Made Lia Oktaviani; I Putu Wahyudi Pratama (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
School-Based Management (SBM) is a form of educational management that gives schools the authority to manage resources independently in order to improve the quality of education. This study aims to analyze the effectiveness of School-Based Management implementation in improving educational quality. The study used a descriptive qualitative approach with a case study design. The population of this study consisted of principals and elementary school teachers in Cluster VIII of Abiansemal District, while the research sample was SD No. 4 Sibangkaja. Data collection techniques included observation, interviews, and documentation. Data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing, combined with SWOT analysis. The findings showed that the implementation of SBM had been quite effective through participatory school management, creative project-based learning, and stakeholder involvement in supporting school programs. However, the implementation of SBM still faced challenges such as limited technological facilities, limited learning time, and differences in students’ abilities. The SWOT analysis indicated that the school has significant opportunities to improve educational quality through collaboration with various parties and the development of innovative learning programs. Therefore, improvements in learning facilities, stronger stakeholder collaboration, and sustainable school program development are needed to support the effectiveness of SBM implementation in improving educational quality.